Limpeza e desinfecção de superfícies hospitalares: subsídio para elaboração e avaliação de rotinas - Rigotti, Marcelo Alessandro (2017)
Contamination of hospital surfaces plays an important role in the spread of infection related to health care. There is still no consensus as to how environmental surfaces should be cleaned and / or disinfected, and the most appropriate methods for assessing the cleaning / disinfection process. There are different systems for monitoring the efficiency of the process of cleaning hospital surfaces: among them, visual inspection, fluorescent marker, adenosine triphosphate by bioluminescence and microbiological cultures. Objectives: 1. To compare the efficiency of three surface friction techniques to reduce organic matter; 2. Evaluate the efficiency of concurrent cleaning / disinfection of operating room surfaces; 3. Evaluate the efficiency before / after cleaning / disinfection of operating room surfaces after review and implementation of an L / D protocol with an emphasis on educational and procedural interventions. Material and Methods: 1. Quantitative, descriptive and exploratory study carried out before and after the cleaning / disinfection process of the bedside tables of the patient unit. Three unidirectional, bi-directional and centrifugal friction techniques were performed individually on each table. For each patient unit and friction technique, a single table and cloth moistened with 70% alcohol (w / v) was used. Organic matter was detected by the presence of adenosine triphosphate by bioluminescence using the 3M ™ Clean-Trace ™ ATP Systems system. 2. A prospective, correlational study developed in the interior of São Paulo, in July 2014. Non - probabilistic sample consisted of the surfaces: surgical table, anesthesia machine, accessory table and counter, being evaluated by visual inspection, microbiological culture and adenosine triphosphate by bioluminescence, at the frequency of one operating room per day. 3. Similar to study 2, but between the months of July and August of 2014. Together, the coordinating nurse of the surgical unit carried out educational intervention and standardization of procedures. Results: 1. For each technique, 13 samples were collected before / after the cleaning / disinfection process, totaling 78 crops. There was no statistical difference between techniques for the removal of organic matter. This study demonstrated that the three surface friction techniques are effective (p <0.05). 2. Twelve samples per surface were collected in 12 days, before and after cleaning / disinfection, totaling 96 samples. The cleaning / disinfection significantly reduced the quantification of adenosine triphosphate and microbial counting of the anesthesia and counter apparatus (p <0.05). The overall rate of cleaned surfaces by visual inspection, microbiological culture and adenosine triphosphate was, before cleaning and disinfection, 37.5%, 10.4% and 12.5%, respectively, and 39.6%, 31, 2% and 70.8% after. 3. Number of samples similar to study 2. Cleaning / disinfection significantly decreased all monitoring parameters for all surfaces. The overall rate of cleaned surfaces by visual inspection, ATP and culture was respectively 47.0%, 37.5% and 22.0% before cleaning and disinfection, and 81.2%, 89.6% and 70.1% after. Conclusions: 1. Further studies considering other indicators and surfaces are needed. 2. The protocol for cleaning / disinfecting operating room surfaces needs to be re-evaluated in order to provide safety to the surgical patient. 3. The elaboration and implementation of the protocol of cleaning / disinfection of the operating room proved to be efficient, since it presented smaller and significant results after the cleaning / disinfection, considering the methods of measurement of the process of cleaning the environmental surfaces.